Modulation by context of a scene in monkey anterior inferotemporal cortex during a saccadic eye movement task - LIMA,BRUSS (2003)
We investigated the effect of a scene on the activity of cells in the anterior inferotemporal (AIT) cortex while the monkey performed a saccadic eye movement (SEM) task with and without the context of a scene (gray frame). Most neurons did not code for the presence of a scene when it appeared alone (monkey free viewing) or when the monkey was fixating. Nevertheless, when a peripheral target was turned on and the monkey had to make a SEM to it, some cells were capable of differentially coding the presence of the scene before and after the saccade.